2022
DOI: 10.3390/nano12030392
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surface Properties of Nanostructured Ceria-Based Catalysts on Their Stability Performance

Abstract: As the poor cycling stability of CeO2 catalysts has become the major obstacle for applications of diesel particulate filters (DPF), it is necessary to investigate how to reduce their structural and compositional changes during soot oxidation. In this study, different ratios of Samarium (Sm) were doped into the lattice of CeO2 nanoparticles to improve the catalytic performance as well as surface properties. The stability was investigated by recycling the catalyst, mixing it with soot again, and repeating the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…A these bands, u0 (882.1 eV), u2 (888.9 eV), and u3 (897.6 eV) were the characteristic ba 3d3/2 spin-orbital components of Ce 4+ , whereas v0 (900.2 eV), v2 (907.2 eV), and v3 (916 were assigned to the 3d5/2 spin-orbital components of Ce 4+ . The u1 (884.7 eV) and v1 eV) bands were attributed to the emissions of 3d3/2 and 3d5/2 spin-orbital of Ce 3+ , r tively [47][48][49][50]. The percentage of Ce 3+ in the CeO2 and CZO was determined from th tion of the sum of the area of total Ce 3+ species (u1 and v1) to the sum of the area of to species [47][48][49].…”
Section: Characterization Of Ru-czo Powdersmentioning
confidence: 99%
“…A these bands, u0 (882.1 eV), u2 (888.9 eV), and u3 (897.6 eV) were the characteristic ba 3d3/2 spin-orbital components of Ce 4+ , whereas v0 (900.2 eV), v2 (907.2 eV), and v3 (916 were assigned to the 3d5/2 spin-orbital components of Ce 4+ . The u1 (884.7 eV) and v1 eV) bands were attributed to the emissions of 3d3/2 and 3d5/2 spin-orbital of Ce 3+ , r tively [47][48][49][50]. The percentage of Ce 3+ in the CeO2 and CZO was determined from th tion of the sum of the area of total Ce 3+ species (u1 and v1) to the sum of the area of to species [47][48][49].…”
Section: Characterization Of Ru-czo Powdersmentioning
confidence: 99%
“…Also, due to their outstanding performance, ionic conductivity, and low operating temperatures (300–600 °C), doped or undoped ceria-based electrolytes are a new study area. CFC device design and ionic conduction are enhanced by surface features that are both faradic and nonfaradic, respectively. Thus, Tm-doped CeO 2 , Gd-doped CeO 2 , Sm-doped CeO 2 , and triple-doped CeO 2 have all been investigated for their surface properties in ceramic fuel cells. Multichannel CFC ionic conduction can be achieved by stepwise doping single, divalent, and trivalent ions. ,, …”
Section: Introductionmentioning
confidence: 99%
“…The development of nanomaterials with different shapes and sizes and which are utilized as effective materials for energy and environmental applications constitutes a challenge for researchers [ 1 , 2 , 3 , 4 , 5 ]. This is because our society totally depends on electronic devices, which are certainly made up of and based on various types of energy-storage devices [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. These devices are assembled with various types of the materials, including metal oxide, hydroxide, metal composites with carbon-based materials such as graphene, conducting polymers, and carbon nanotubes.…”
mentioning
confidence: 99%
“…This Special Issue also collected various research articles addressing catalysis, which is used in different applications; for example, Boyu Li, et al [ 8 ] reported the stability performance of a ceria-based catalyst. The poor performance of the ceria catalyst in purification industries especially used in diesel particulate filtration due to structural changes occurred during the soot oxidation of the diesel particulate.…”
mentioning
confidence: 99%